Teacher work environments are toddler learning environments: teacher professional well-being, classroom emotional support, and toddlers' emotional expressions and behaviours. Issue 11 (2nd November 2017) - Cassidy, Deborah J.; King, Elizabeth K.; Wang, Yudan C.; Lower, Joanna K.; Kintner-Duffy, Victoria L.
ABSTRACT: The current study examines the professional well-being of teachers, the classroom emotional support, and the emotional experiences of toddlers in their care. Professional well-being of teachers is conceptualized to include teacher feelings about their work, autonomy in decision-making, actual wages, and perceptions of fairness of wages within the programme as well as within the early childhood profession at large. The study empirically supports relationships among teacher professional well-being, classroom emotional support, and the emotional expressions and behaviours of toddlers. Early childhood policy implications regarding teacher professional well-being and toddler classroom emotional environments are discussed.